Recopilación de información para la implementación de un sistema de gestión de ordenamiento territorial para el cantón de Alvarado, Cartago, Costa Rica - Acuña-López, Sofía (Instituto Tecnológico de Costa Rica, 2017)
In the research project of the Instituto Tecnológico de Costa Rica (ITCR), which was completed in 2017, were made participatory workshops and they determined that the canton of Alvarado had a technological gap with respect to other cantons of the province of Cartago, to manage the land use planning, because the economic and technological resources are missing. In order to solve this deficiency, the objective of gathering information for the implementation of a land management system was raised. A diagnosis was made in the Municipality, information necessary for the calculation of indicators of the Plan GAM 2013-2030 (2014) was generated, which was organized in folders, and a data catalog was created, besides the metadata were created too. The result obtained was a database with information for the Municipality of Alvarado, ordered, simple, easy to use, which consists of seven folders, with a total of eleven files. The compilation of the information allowed to know the strengths and weaknesses of the information available in the Municipality of Alvarado. In addition, the list of indicators proposed in previous projects was improved, adapting them to an integral dense centrality of the peripheral type and to a canton where the macrozone of protection and preservation predominates.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Ordenamiento territorial; Indicadores; Brecha; Datos; Ingeniería forestal